Pengaruh Motivasi Belajar dan Disiplin terhadap Hasil Belajar Siswa Kelas X Pada Mata Pelajaran Akidah Akhlak di MA Nurul Jihad Tembilahan Hulu - Hasnawati, Hasnawati; Za’ba, Nasir (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to analyze whether academic motivation and discipline partiallyand simultaneously affect students' academic performance. This study is a quantitative study with a path analysis design used to examine direct or indirect effects between study variables. The subjects of this study were teachers and students of the Aqidah Akhlak department at MA Nurul Jihad Tembilahan Hulu. Data collection was used in the form of questionnaires and tests. And the data analysis used by the researchers is multiple linear regression analysis. The results of this study are as follows: 1) there is no significant effect between learning motivation and student learning outcomes, 2) there is a significant effect between learning discipline and student learning outcomes, and 3) there is an effect between learning motivation and learning discipline on student learning outcomes.